The Recombinant Eg.P29-Mediated miR-126a-5p Promotes the Differentiation of Mouse Naive CD4+ T Cells via DLK1-Mediated Notch1 Signal Pathway - Du, Xiancai; Zhu, Mingxing; Zhang, Tingrui; Wang, Chan; Tao, Jia; Yang, Songhao; Zhu, Yazhou; Zhao, Wei (Frontiers in Immunology, 2022)
Cystic Echinococcosis (CE) is a worldwide spread zoonotic parasitic diseases caused by Echinococcus granulosus (Eg), which seriously endangers human health and obstructs socioeconomic development. A number of recombinant vaccines based on Eg are used to evaluate the effectiveness against infection. Our previous report showed that recombinant Eg.P29 (rEg.P29) has a marvelous immunoprotection and can induce Th1 immune response. Furthermore, the data of miRNA microarray in mice spleen CD4+ T cells showed that miR-126a-5p was significantly elevated one week after immunization by using rEg.P29. Therefore, in this perspective, we discussed the role of miR-126a-5p in the differentiation naïve CD4+ T cells into Th1/Th2 under rEg.P29 immunization and determined the mechanisms associated with delta-like 1 homolog (DLK1) and Notch1 signaling pathway. One week after P29 immunization of mice, we found that miR-126a-5p was significantly increased and DLK1 expression was decreased, while Notch1 pathway activation was enhanced and Th1 response was significantly stronger. The identical conclusion was obtained by overexpression of mmu-miR-126a-5p in primary naïve CD4+ T cells in mice. Intriguingly, mmu-miR-126a-5p was significantly raised in serum from mice infected with protoscolex in the early stages of infection and markedly declined in the late stages of infection, while has-miR-126-5p expression was dramatically reduced in serum from CE patients. Taken together, we show that miR-126a-5p functions as a positive regulator of Notch1-mediated the differentiation of CD4+ T cells into Th1 through downregulating DLK1 in vivo and in vitro. Hsa-miR-126-5p is potentially a very promising diagnostic biomarker for CE.